2012
DOI: 10.5005/jp-journals-10024-1174
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Shear Bond Strength of Metal Brackets Bonded to Porcelain Surface using Different Surface Conditioning Methods: An in vitro Study

Abstract: Aim: To evaluate and compare the shear bond strength of metal brackets bonded to ceramic surfaces using different conditioning methods and to assess the site of bond failure after debonding. Materials and methods:A total of 70 ceramic surfaces were produced with uniform shape, size and composition. The samples were divided into 7 groups (each of 10 samples).Group 1 was the control group (untreated surface); in group 2 the surface were roughened with a diamond bur; in group 3 the surface were etched with hydrof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 11 publications
3
25
0
1
Order By: Relevance
“…It is possible that the micro-retentions generated by CoJet system, whose particles are 30 ìm in size, could be lower than those created by the aluminum oxide blasting (50 ìm particles). These findings agree with Girish et al 21 (2012), who reported that blasting with larger particles (110 ìm) produced higher bond strength values than those found with CoJet. Ozcan 22 (2014), who evaluated the CoJet in ceramic, metal-ceramics, metal-mechanics and metallic substrates, achieved the best results with metallic substrates.…”
Section: Shear Bond Strength Of Ceramic Brackets After Different Pre-supporting
confidence: 92%
“…It is possible that the micro-retentions generated by CoJet system, whose particles are 30 ìm in size, could be lower than those created by the aluminum oxide blasting (50 ìm particles). These findings agree with Girish et al 21 (2012), who reported that blasting with larger particles (110 ìm) produced higher bond strength values than those found with CoJet. Ozcan 22 (2014), who evaluated the CoJet in ceramic, metal-ceramics, metal-mechanics and metallic substrates, achieved the best results with metallic substrates.…”
Section: Shear Bond Strength Of Ceramic Brackets After Different Pre-supporting
confidence: 92%
“…17 Aluminum oxide sandblasting has been widely used to promote micromechanical retention of ceramics (madani 2000). Many studies 27,28 have shown that Al 2 O 3 sandblasting, combined with silane, significantly increased the bond strength of bracket-to-porcelain surface. Girish et al 27 showed that 50 lm Al 2 O 3 SB for 10 sec without thermocycling enhanced to SBS value (15.18 MPa).…”
Section: Discussionmentioning
confidence: 98%
“…Many studies 27,28 have shown that Al 2 O 3 sandblasting, combined with silane, significantly increased the bond strength of bracket-to-porcelain surface. Girish et al 27 showed that 50 lm Al 2 O 3 SB for 10 sec without thermocycling enhanced to SBS value (15.18 MPa). This finding is concurrent with results from the current study, because thermocycle can decrease the SBS value.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This mechanical preparation has been shown to increase adhesion to these surfaces by as much as 100%. 15 After microetching a porcelain crown, the surface was chemically etched with 8% hydrofluoric acid to further increase the adhesive strength. Silane then was applied followed by a bonding adhesive.…”
Section: S58mentioning
confidence: 99%